Groundwater Identification Using the Geoelectric Method (Electrical Resistivity TomographyERT) For the Utilization of Mining Areas - M. Abdul Abdul Rahman Salim; Dasapta Erwin Irawan; Imam Achmad Sadisun; Kurniawan Kurniawan; Bonanza Herlambang (Geological Engineering Department Universitas Gadjah Mada, 2025)
Research conducted in Pomalaa Subdistrict, Kolaka Regency, Southeast Sulawesi, aimed to identify the potential and characteristics of groundwater in an area with complex geological conditions, dominated by ultramafic and sedimentary rocks. To achieve this objective, a multidisciplinary approach was used, including geological and hydrogeological mapping and direct geoelectric testing in the field. One of the main methods used in this study was a geophysical technique called Electrical Resistivity Tomography (ERT), which is capable of producing two-dimensional subsurface images based on variations in the electrical resistivity of soil and rock. The analysis results show that ultramafic rocks in this region have the potential to be free aquifers, with moderate to high hydraulic conductivity values, making them potentially usable as a source of clean water for the domestic needs of the local community. Meanwhile, the southwestern zone, which is composed of sedimentary rocks, shows the presence of a confined aquifer with high permeability and a relatively low water table, making it a more accessible source of groundwater. The integration of all geological, hydrogeological, and geophysical data provides a comprehensive picture of the distribution and quality of groundwater in the Pomalaa region. These findings provide a strong scientific basis to support strategies for the conservation and sustainable use of groundwater resources, as well as to make